CONCEPTS IN REGRESSION ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
Regression analysis is a set of statistical techniques that may be used to makejudgements about the relationships between variables. Regression analysis is now the mostwidely used data analysis tool, with applications in practically every field of study, includingsocial, physical and Biological Sciences, business and engineering. As a result, the purpose ofthis text is to develop the underlying theory of this key statistical method and to illustrate itwith examples drawn from economics, demography, engineering and biology